Pengaruh Eksistensi Bahasa Gaul pada Remaja Jakarta Selatan terhadap Bahasa Nasional - Lituhayu, Anindita Nareswari; Siagian, Irwan (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to examine youth slang in South Jakarta on the influence of the national language. This study uses a qualitative method with descriptive techniques, namely describing of analyzing through observational data sources from South Jakarta adolescents which contain subjective values regarding the phenomenon of existence to be studied. Observation is used with data collection techniques which are interviewing and making observations were used, followed by recording of the situation. The data of this research is a dialogue between teenagers in South Jakarta using fragments of words, phrases, clauses and sentences. This analysis produces data from one source. The outcome of this research are that there is a diversity of slang vocabulary, the use of slang affects the existence of the national language among adolescents in South Jakarta, and the creation of slang is obtained through absorption from English, acronyms, diglossia, or from Betawi.